1999
DOI: 10.1161/01.str.30.2.378
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Silent Cerebral Infarcts in Subcortical White Matter and Basal Ganglia

Abstract: Background and Purpose-The purpose of this study was to clarify whether the relevant risk factors for silent cerebral infarcts (SCIs) in subcortical white matter (WM) are different from those in the basal ganglia (BG). Methods-Subjects of this study were 219 adults without a history of stroke or transient ischemic attack and without any abnormality on a neurological examination who consecutively visited the neurology service in our hospital between January 1994 and November 1997 requesting medical evaluation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
84
3
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 44 publications
(49 reference statements)
5
84
3
2
Order By: Relevance
“…The pathogenesis of SLI has been considered to differ between the white matter infarction and the basal ganglia infarction. Recent studies have shown that the relative risk factors are different between the white matter infarction and the basal ganglia infarction (18). Thus high blood pressure was a predominant risk factor for white matter infarction, but basal ganglia infarction was associated with systemic atheroscleroses such as coronary artery disease and carotid artery stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of SLI has been considered to differ between the white matter infarction and the basal ganglia infarction. Recent studies have shown that the relative risk factors are different between the white matter infarction and the basal ganglia infarction (18). Thus high blood pressure was a predominant risk factor for white matter infarction, but basal ganglia infarction was associated with systemic atheroscleroses such as coronary artery disease and carotid artery stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…Lacunar infarcts were defined as areas of low signal intensity (3-to 15-mm diameter) on T1-weighted images and of high intensity on T2-weighted and FLAIR images. PVHs were defined as white matter hyperintensities depicted on T2-weighted and FLAIR images 15,16 in contact with the ventricular wall. PVH was further classified into five grades according to the Japanese Braindock Guidelines 2003, 17 namely grade 0, absent or only a 'rim'; grade 1, limited lesion-like 'caps'; grade 2, irregular 'halo'; grade 3, irregular margins and extension into the deep white matter; and grade 4, extension into the deep white matter and subcortical portion.…”
Section: Study Subjectsmentioning
confidence: 99%
“…The MRI findings were classified according to the following parameters: PVH, DSWMH, and état criblé, according to the Japanese Braindock Guidelines 2003 (15). PVH and DSWMH were defined as exhibiting high intensity lesions by T2-weighted and proton density images or by fluid-attenuated inversion recovery (FLAIR) (16,17), and low intensity determined by T1-weighted images. État criblé was assessed at the basal ganglial level, as high-intensity signals evaluated by T2-weighted images (18).…”
Section: Mrimentioning
confidence: 99%